The Predictive Value of Pre-Operative Symptoms Including Upper Gastrointestinal Endoscopy Before Laparoscopic Cholecystectomy for Elective Symptomatic Cholecystolithiasis - Karmacharya, A; Malla, BR; Joshi, HN; Gurung, RB; Rajbhandari, M (Kathmandu University Medical Journal, 2015)
Background It has always been a challenge to distinguish between upper gastrointestinal symptoms due to gall stones or any other causes. The persistence of abdominal symptoms even after cholecystectomy is highly discouraging for surgeons. Objective To evaluate the value of preoperative (UGE) as a routine investigative tool in patients with gall stone disease and to assess the outcome of cholecystectomy in patients with gallstones on preoperative abdominal symptoms. Methods This is a prospective study conducted on 96 cases at the Department of Surgery, Dhulikhel Hospital among ultrasonographically proven gall bladder stones irrespective of age and sex. After the examination, all the patients were subjected to UGE, and biopsy were obtained for histopathology if required. The statistical analysis were performed using spss version 16. Results Out of total patients, 84(87.5%) were females and 12(12.5%) were males with a M: F ratio of 1:7. Both the sexes were comparable in age groups. Out of total 96 patients, 53(55.2%) presented with typical pain and 43(44.8%) presented with atypical pain. All the patients were subjected to upper gastrointestinal endoscopy (UGE) and 53(55.2%) had normal findings and 43(44.8%) had various lesions. Patients with typical pattern of pain had normal endoscopic findings and those with atypical pain had pathology in upper gastroendoscopy (p<0.001). Serious pathology resulting to change of the planned treatment was found in three cases (3.12%). Among them two had gastric carcinoma and one had active peptic ulcer disease. The relief rate after the cholecystectomy was significant in patients with typical pain than among those with atypical pain (p<0.001). The commenest post cholecystectomy symptoms were heart burn (10%), abdominal discomfort (9%) and dyspepsia (7%). Conclusion Presence of atypical pain in patients with gall stones is highly likely to have other coexisting upper gastrointestinal pathologies. Hence, upper gastrointestinal endoscopy prior to elective cholecystectomy in patients with gall stones can be clinically helpful. Kathmandu Univ Med J 2013; 11(4): 300-304